Broadband single molecule SERS detection designed by warped optical spaces - Peng Mao (Nature Portfolio, 2018)
In standard SERS the probability for the molecules to reach tiny hotpot regions is low. Here, the authors introduce an approach based on warped spaces that offers a strategy to manipulate hotspots of metallic nanostructures, resulting in large broadband enhancements in both the magnitude and the volume size.